2017
DOI: 10.1021/acs.jced.7b00454
|View full text |Cite
|
Sign up to set email alerts
|

The New Method for Correlation and Prediction of Thermophysical Properties of Fluids. Critical Temperature

Abstract: On the basis of the linear free energy relationships theory and thermodynamics formulas, a new method predicting critical temperature (T c) of pure fluids is proposed for the first time. Sixteen homologues of 616 substances have been regressed and correlation equations between T c and molecular descriptors are obtained. The mean relative deviations of the 16 equations are from 0.01% to 2.73%, and most of them are under 2%. In addition, the squared correlation coefficients are from 0.90 to 0.98. Moreover, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Abraham solute parameters predicted using the SoluteML model by Chung et al are explored as additional molecular features. The Abraham parameters are chosen as one of the optional features for our models as a correlation by Li et al has revealed a direct relationship between T c and the Abraham parameters. The Abraham parameters consist of five descriptors, E , S , A , B , and L , each of which is associated with a different physical property of a compound .…”
Section: Methodsmodelsmentioning
confidence: 99%
“…Abraham solute parameters predicted using the SoluteML model by Chung et al are explored as additional molecular features. The Abraham parameters are chosen as one of the optional features for our models as a correlation by Li et al has revealed a direct relationship between T c and the Abraham parameters. The Abraham parameters consist of five descriptors, E , S , A , B , and L , each of which is associated with a different physical property of a compound .…”
Section: Methodsmodelsmentioning
confidence: 99%
“…Some examples include definition of group interaction contributions (Marrero-Morejon and Pardillo-Fontdevila, 1999), identification of the specific positions of groups, elements and chemical bonds, etc. (Li et al, 2017). The method of Marrero and Gani and the older method of Constantinou and Gani (Constantinou and Gani, 1994), which this year will mark 25 years of service but still preferred by many, are among the most used GC methods, chosen for biofuel process design (Garcia et al, 2010;Arvelos et al, 2014).…”
Section: Group Contribution Methods For Biofuels Process Designmentioning
confidence: 99%
“…As a simple pen-and-paper structure-property relationship (SPR) method [7][8][9] , group contribution (GC) method is based on the principle of group addition 10 . The group contribution method is widely used to predict various thermodynamic properties of organic compounds, such as critical temperature [11][12][13][14][15][16][17][18][19][20] , critical pressure 13,[21][22][23][24] , critical volume 17,25 and normal boiling point 10,26 . Among GC approaches, Joback 27 , C-G (Constantinou and Gani) 28 and M-G (Marrero and Gani) 29 methods are classical GC methods.…”
Section: Introductionmentioning
confidence: 99%